Klapskate - Duncan, D.
Author has completed an in depth research project into the Klapskate and presents it's rsults here. Table of Contents: Introduction Theory of the Klapskate The Development of the Klapskate The Road to Success: From Prototype to Skating Essential Impact of the Klapskate Advantages and Disadvantages of the Klapskate Advantages Disadvantages Skaters' Impressions What the future holds Conclusion References Published References Questionnaire respondents Photos Statistics